Exploring the potential effects of Lactococcus lactis D4 on the proliferation, apoptosis, and inflammatory responses in colorectal cancer cells - Rivai, Muhammad I.; Lusikooy, Ronald E.; Putra, Andani E.; Elliyanti, Aisyah; Sukma, Ade (Narra J, 2025)
Lactococcus lactis D4 is a probiotic produced through the fermentation of buffalo milk in bamboo, namely "dadih", a traditional food from West Sumatera, Indonesia. To the best of our knowledge, no specific research has investigated the effects of L. lactis D4, derived from dadih extraction, on colorectal cancer or its potential clinical applications. Therefore, the aim of this study was to evaluate the potential of L. lactis D4 from dadih to inhibit colorectal cancer growth in rat models, with a focus on its effects on cell proliferation, apoptosis, and inflammatory responses. An in vivo study was conducted using 37 male Sprague-Dawley rats, allocated into five groups: (1) control (no treatment), (2) dysplasia (induced with 1,2-dimethylhydrazine until dysplasia developed), (3) dysplasia + L. lactis D4 (induced with 1,2-dimethylhydrazine, then treated with L. lactis D4 after dysplasia confirmation), (4) cancer (induced with 1,2-dimethylhydrazine until cancer was confirmed), and (5) cancer + L. lactis D4 (induced with 1,2-dimethylhydrazine until cancer was confirmed, then treated with L. lactis D4 for 15 days). The effects of L. lactis D4 on cancer progression were assessed through immunohistochemical analysis of cell proliferation (cyclin D1, Bcl-2), apoptosis (p53, caspase-3), and inflammation (nuclear factor-κB (NF-κB) and cyclooxygenase-2 (COX-2)). This study found that L. lactis D4 treatment reduced adenocarcinoma and dysplasia severity in colorectal cancer models through significant reduction in cyclin D1, Bcl-2, NF-κB, and COX-2 expression observed across all groups (p<0.01), although changes in dysplasia and cancer subgroups were not statistically significant (p>0.05). No statistically significant change was noted in p53 expression (p=0.518), whereas caspase-3 expression varied significantly across groups (p=0.010). In conclusion, L. lactis D4 reduces the expression of cyclin D1, Bcl-2, NF-κB, and COX-2 proteins, offering insights into its potential to modulating proliferation and inflammation in colorectal cancer growth.